A Study on the Nature of Association between Demodex Mites and Bacteria Involved in Skin and Meibomian Gland Lesions of Demodectic Mange in Cattle - Mukhtar Taha Abu-Samra; Yassir Adam Shuaib (Veterinary Medicine International)
The nature of association between Demodex mites and bacteria involved in bovine demodectic mange lesions and the normal flora inhabiting the skin of noninfected animals was investigated. Demodex bovis and D. ghanensis mites were isolated from the infected purulent material extracted from skin and meibomian gland lesions, respectively. The mites could not be demonstrated in skin brushings or impression smears from the eyes of noninfected cattle. Pathogenic bacteria (Staphylococcus aureus and Streptococcus pyogenes (Group A)) and opportunistic organisms (Proteus vulgaris, Pseudomonas aeruginosa, Staphylococcus epidermidis, and Trueperella pyogenes) were isolated from skin lesions of demodectic mange, and Moraxella bovis and Staphylococcus aureus were isolated from meibomian gland lesions. Bacillus subtilis, Escherichia coli, Proteus vulgaris, Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus pyogenes (Group A) were isolated from skin brushings from noninfected cattle. The nature of association between Demodex mites and bacteria in demodectic mange lesions is synergistic and of equal significance. Pathogenic and opportunistic bacteria facilitated the establishment of Demodex mites in the lesions produced and provided an excellent microclimate for the mites to propagate and reproduce, resulting in severe and progressive disease. The “high-turnover” granulomatous reaction which characterized the histopathological changes proved that Demodex mites and associated bacteria were persistent and immunogenic.